Significant seasonal evolution of sediment transport with mild sea conditions in the eastern Jiangsu coast of China - Huang, Huiming; Wang, Sheng; Lan, Yinyu; Zhang, Yu (Frontiers in Marine Science, 2025)
The eastern coastal area of Jiangsu, China, is characterized by a silty and muddy coast, exhibiting substantial seasonal variations in suspended sediment transport within the sea area. This study draws from the quasi-synchronous hydrological and sediment observation data from various stations in the eastern Jiangsu coast during the spring tide cycle in the summer of 2006 and the winter of 2007. Then, the study analyzes the seasonal variation characteristics and mechanisms of the plane and vertical distribution of sediment transport and further examines their correlations with tidal current, wave, and seawater temperature. The findings reveal an “M-shape” distribution pattern in the plane of sediment concentration both in summer and winter, with two pronounced peaks in the Binhaigang and Jianggang sea areas in the coastal direction and a gradual decline in the offshore direction. Meanwhile, the vertical distribution of sediment concentration exhibited greater uniformity in profile during winter than during summer. Under mild sea conditions in the Jiangsu coast, the action weights of the influencing factors affecting the plane distribution of sediment concentration are in the following order: tidal current > wave > seawater temperature. From Lianyungang to Sheyanggang, the action weights of the influencing factors affecting the seasonal variation of plane distribution of sediment concentration are as follows: tidal current > wave > seawater temperature; from Sheyanggang to Lvsigang, the action weights of the influencing factors affecting the seasonal variation of plane distribution of sediment concentration are wave in the following order: wave > tidal current > seawater temperature. Meanwhile, the action weights of the influencing factors affecting the seasonal variation of sediment concentration profile area are as follows: seawater temperature > wave > tidal current. These results differ from the previous understanding about seasonal variation of sediment transport in silty and muddy coasts, which shows that waves play a dominant role in influencing the seasonal change of sediment transport in coastal waters.